NON-COMPETE AGREEMENTS: CIVIL LAW ASPECT - Anton Guzhva (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2022)
The article is devoted to the problems of legal regulation of non-compete  agreements in the civil law of Ukraine. The author considers non-compete agreements as one of the types of negative obligations. Emphasis is placed on the insufficient regulation of the research subjects in the national legislation.